Global research trends of acupuncture therapy on cancer pain: A bibliometric and visualized study - Li, Chunyu; Zhao, Can; Zhao, Jingjing; Wang, Min; Luo, Furong; Zhou, Jianwei (Frontiers in Oncology, 2023)
Background The number of publications on acupuncture for cancer pain is increasing rapidly with an upward tendency. Considering that no bibliometric articles related to this topic have been published yet. It is necessary to evaluate the global scientific output of research in this field, and shed light on the direction of clinical cancer pain management in the future. Methods Research publications regarding acupuncture on cancer pain from inception to 2022 were downloaded from the Web of Science Core Collection. Bibliometric analyses were performed using CiteSpace software, the bibliometrix R package, and VOSviewer software. Network maps were generated to assess the collaborations between different countries, institutions, authors, and keywords. And clusters map was generated to evaluate reference. Results A total of 790 articles related to acupuncture therapy for cancer pain were identified. We observe that the number of publications is gradually increasing over time. China and the United States were the main contributors. Mem Sloan Kettering Canc Ctr (38 papers) and Beijing Univ Chinese Med (28 papers) contributed the most publications, becoming the leading contributors in this field. Although J Clin Oncol (28 articles) ranked ninth in terms of publication volume, it was the journal with the most citations and the highest number of IF (50.717) and H-index (494) at the same time. MAO J from Mem Sloan Kettering Canc Ctr was the most prolific author (23 articles). The main hot topics included matters related to acupuncture (239 times), pain (199 times), management (139 times), quality of life (107 times), electroacupuncture (100 times), and breast cancer (82 times). Conclusion Our bibliometric analysis provides a comprehensive overview of the development of acupuncture for cancer pain, enabling relevant authors and research teams to identify the current research status in this field. At the same time, acupuncture for breast cancer (BC) pain, aromatase inhibitor-induced arthralgia (AIA), and chemotherapy-induced peripheral neuropathy (CIPN) may soon become prospective focus.